PENGARUH PERHATIAN ORANG TUA DAN INTENSITAS BELAJAR TERHADAP HASIL BELAJAR PECAHAN KELAS III SD SE-KECAMATAN PADURESO - Septiningsih, Susi (KALAM CENDEKIA PGSD KEBUMEN, 2015)
ABSTRACT: The Influence of Parent?s Attention and Intensity of learning on the Result of Decimal Fraction Learning of III Grade Elementary School Padureso District. The purpose of this research to determine whether there is influence of interaction between the parent?s attention and intensity of learning on the result of decimal fraction learning of III grade elementary school District Padureso. This research is a quantitative research using Expost Facto method. Result concluded that (1) There is the influence of parent?s attention on the result of decimal fraction learning of III grade elementary school Padureso District; (2) There is the influence of Intensity learning on the result of decimal fraction learning of III grade elementary school Padureso District; (3) There is an interaction influence between of parent?s attention and intensity of learning on the result of decimal fraction learning of III grade elementary school Padureso District. Key words: parent?s attention, , intensity of learning, the result of decimal fraction learning ABSTRAK: Pengaruh Perhatian Orang Tua dan Intensitas Belajar Terhadap Hasil Belajar Pecahan Kelas III SD Se-Kecamatan Padureso. Tujuan penelitian ini adalah untuk mengetahui ada tidaknya interaksi pengaruh antara Perhatian orang tua dan intensitas belajar terhadap hasil belajar pecahan kelas III SD se-Kecamatan Padureso. Penelitian ini merupakan penelitian kuantitatif dengan metode ekspost facto. Hasil penelitian ini dapat disimpulkan bahwa (1) Ada pengaru perhatian orang tua terhadap hasil belajar pecahan kelas III SD se-Kecamatan Padureso; (2) Ada pengaruh intensitas belajar terhadap hasil belajar pecahan siswa kelas III SD se-Kecamatan Padureso; (3) Ada interaksi pengaruh antara perhatian orang tua dan intensitas belajar terhadap hasil belajar pecahan kelas III SD se-Kecamatan Padureso. Kata Kunci: perhatian orang tua, intensitas belajar, hasil belajar pecahan